Comparison of anthrophometric data of IPT student with non student with ages of 18-25 years / Mohamed Azmi Mohamed Ripin and Norhafizah Rosman - Mohamed Ripin, Mohamed Azmi; Rosman, Norhafizah (2012)
Nowadays, industrial have faced the lacks of anthropometric data for making furniture. Anthropometry can be defined as a study of a human body dimension. Anthropometric data is used in designing area of clothing design, workspace design, environment design, design of equipment, tools, and machinery, and also in designing consumer product design. Anthropometry data is used in application to design something that will give comfortable to people with their working space to prevent danger, damages, and any unnecessary activity. The objective of this study is to gather the data of human body measurement as a collection for local anthropometric data for industrial to making furniture based on the anthropometric measurement. The measurement of human body was gather from UITM student and has been compare with non-student, that are working around Bandar Jengka region. As a conclusion, from the collecting data from my respondent, we can gather new data for anthropometric measurement for industrial furniture making. The ranges between the two variables are not very different, only small standard deviation is being gain from the result has been analyzed.